An Examination of the Month-of-the-year Effect at Damascus Securities Exchange - Mouselli, Sulaiman; Al Samman, Hazem (International Journal of Economics and Financial Issues, 2016)
This paper explores the existence of the month-of-the-year effect in a newly established exchange of Damascus Securities Exchange (DSE). It employs Ordinary Least Squares Estimates (OLS) and dummy variables for the whole working period of the exchange from 2010 to 2015. This paper confirms the existence of positive and significant returns during May compared to remaining months. Average returns in May are six percent higher than average returns during the rest of the year. A possible explanation for May effect is dividend month premium suggested by <!–[if supportFields]>ADDIN CSL_CITATION "citationItems" : [ "id" : "ITEM-1", "itemData" : "DOI" : "10.1016/j.jfineco.2013.02.015", "ISBN" : "0304405X", "ISSN" : "0304405X", "abstract" : "We find an asset pricing anomaly whereby companies have positive abnormal returns in months when they are predicted to issue a dividend. Abnormal returns in predicted dividend months are high relative to other companies and relative to dividend-paying companies in months without a predicted dividend, making risk-based explanations unlikely. The anomaly is as large as the value premium, but less volatile. The premium is consistent with price pressure from dividend-seeking investors. Measures of liquidity and demand for dividends are associated with larger price increases in the period before the ex-day (when there is no news about the dividend) and larger reversals afterward. ?? 2013 Elsevier B.V.", "author" : [ "dropping-particle" : "", "family" : "Hartzmark", "given" : "Samuel M.", "non-dropping-particle" : "", "parse-names" : false, "suffix" : "" , "dropping-particle" : "", "family" : "Solomon", "given" : "David H.", "non-dropping-particle" : "", "parse-names" : false, "suffix" : "" ], "container-title" : "Journal of Financial Economics", "id" : "ITEM-1", "issue" : "3", "issued" : "date-parts" : [ [ "2013" ] ] , "page" : "640-660", "publisher" : "Elsevier", "title" : "The dividend month premium", "type" : "article-journal", "volume" : "109" , "uris" : [ "http://www.mendeley.com/documents/?uuid=96761255-d802-4789-b411-c5f89e99f268" ] ], "mendeley" : "formattedCitation" : "(Hartzmark & Solomon 2013)", "manualFormatting" : "(Hartzmark & Solomon, 2013)", "plainTextFormattedCitation" : "(Hartzmark & Solomon 2013)", "previouslyFormattedCitation" : "(Hartzmark & Solomon 2013)" , "properties" : "noteIndex" : 0 , "schema" : "https://github.com/citation-style-language/schema/raw/master/csl-citation.json" <![endif]–>Hartzmark & Solomon (2013)<!–[if supportFields]><![endif]–>. Keywords: stock market efficiency, calendar seasonality, month-of-the-year effect, Damascus Securities Exchange. JEL Classifications: G11, G14, G19